"Sorry for Congo, Let's Make Amends": Belgians' Ideological Worldviews Predict Attitudes Towards Apology and Reparation for its Colonial Past. Issue 1 (20th August 2021) - Van Assche, Jasper; Roets, Arne; Haesevoets, Tessa; Noor, Masi
In light of the recent steps Belgium has made towards reconciling with its colonial history in Congo (e.g., the King's letter of regret, and the removal of some colonial statues), we examined how Belgians differ in their attitudes towards an official apology, towards (symbolic) reparations (e.g., renaming streets), and towards raising more awareness about the colonial past (e.g., more detailed information in educational books) as a function of their ideological worldviews. We hypothesized that authoritarianism and group dominance would negatively predict these outcome variables, while particularly universal-diverse orientation and egalitarianism would predict them positively. We further hypothesized that these relations would be mediated by relevant intergroup emotions (i.e., group-based guilt, shame, and anger, and especially outgroup empathy). Path model analyses on a sample of 258 Flemish-speaking students provided support for our predictions: (1) universal-diverse orientation was the strongest predictor of all intergroup emotions, (2) empathy—and to a lesser extent group-based anger—were the strongest direct predictors of attitudes towards apologizing, reparation, and awareness, and (3) empathy was the most important mediator explaining the associations of universal-diverse and egalitarian orientations with the outcomes. We discuss the implications of our findings for the current debate regarding reconciliation between groups with a history of colonialism.